KESETARAAN GENDER DAN PEMBERDAYAAN PEREMPUAN DI INDONESIA: KEINGINAN DAN KENISCAYAAN PENDEKATAN PRAGMATIS (STUDI TERHADAP UKM CIREBON HOME MADE) - Erna Ermawati Chotim (AKSELERASI: Jurnal Ilmiah Nasional, 2020)
Promoting gender equality has become a globally recognized and accepted reality. Gender issues have also been identified as essential for the achievement of national development goals. In fact, the achievement of gender equality is seen not only as an end in itself, but also as a catalyst and sine qua non for the achievement of sustainable development. This study tries to assess the level of achievement of gender equality and women's empowerment using three important indicators, namely: participation in education at the primary, secondary and tertiary levels, employment and political decision-making, utilizing valuable secondary data sources. This study uses a qualitative method which is analyzed with a descriptive approach. The resource person is the owner of Cirebon Home Made. At the heart of the problem of gender inequality in Indonesia is the dilemma of the Indonesian government to take a decision to reduce the problem of expanding the level of capacity needed to increase the opportunity to accommodate the different needs of the two. Para also argues that the achievement of gender equality in Indonesia, which has been limited by time, will be a mirage due to multidimensional inhibiting factors. This research rests on the actualization of gender equality and women's empowerment on the desires and necessities of a pragmatic approach.